Energy technologies for pumped groundwater irrigation - spread, opportunity, and challenges - Shrestha, Shisher (2024)
According to Kansakar (2006), only 18% of Tarai farms used GW irrigation. However, this number rose to 30% in the 2011 Agriculture Census and 41.7% in the most recent Agriculture Census. Enormous energy is needed to pump the GW to the surface.